DIAGNOSTIC ACCURACY OF FINE NEEDLE ASPIRATION OF THYROID NODULE VERSES BIOPSY IN THYROID LESIONS - Khan, Inamullah; Naz, Salma; Akhter, Zahid Mehmood; Aziz, Nasir (Journal of Ayub Medical College Abbottabad, 2010)
Bakground: FNA biopsy of thyroid is a rapid, minimally invasive, and cost effective first line procedure in the evaluation of thyroid nodule. This study was conducted to evaluate the cytological accuracy, sensitivity and specificity of fine needle aspiration (FNA) of solitary thyroid nodules in correlation with post-surgical histological findings. Methods: This retrospective study was carried out at Department of Pathology, Abbottabad International Medical College, Abbottabad from January 2009 to December 2010. A total of 81 patients with clinically palpable solitary thyroid nodule were included in the study. Thyroid function tests were initially performed followed by FNA of thyroid nodules later operated and histopathological examination was conducted on the excised nodules. FNA diagnoses were correlated with the histological findings. The accuracy, sensitivity and specificity of the procedure were determined. Results: Out of 81 cases, 5 (6.2%) were unsatisfactory and 76 cases were satisfactory for cytological evaluation. Cytohistopathological correlation was carried out for these cases. The study showed a diagnostic accuracy of 93% with sensitivity and specificity rates of 75% and 96% respectively. Positive predictive value is 81% and negative predictive value is 95%. Conclusion: Fine needle aspiration (FNA) has evolved as an accurate and sensitive diagnostic tool for the initial screening of patients with thyroid nodules, and has reduced the need for unnecessary surgery. Keywords: Thyroid nodule, TSH, fine needle aspiration (FNA)